PERANCANGAN DAN UJICOBA SISTEM KEAMANAN WEB SERVICE DENGAN METODE WS-SECURITY - Muzakir, Ari (JURNAL ILMIAH MATRIK, 2013)
Web service uses XML technology to exchange data in. Form of security is applied to web services is to use public-key cryptography techniques. The attack can be a reconnaissance, destruction or theft of data. The implementation was done by using the security library will provide facilities in developinga. Web security service for the library support XMLSEC as library supporters and library class_wssthat have been builtable to overcome the problem of security on the transport path, especially forauthentication, authorization, and confidentiality request SOAP message. Model WS-Security usingXMLSignature, XMLEncryption, andSecurityTokenwhich utilizesthe cryptographic algorithm RSA with1024 bitkey lengt hto provide protection against transmission of data between client and server web service. The results obtain edare SOAP request messages encrypted and decryptedable to pitch well and signed and checked their authenticity. Keywords:Web Service Security, XML Signature, XML Encryption, Security Token.